2013
DOI: 10.1016/j.ijmyco.2013.04.006
|View full text |Cite
|
Sign up to set email alerts
|

Alteration of human macrophages microRNA expression profile upon infection with Mycobacterium tuberculosis

Abstract: This study signifies the miRNA host response upon intracellular mycobacterial infection in macrophages, providing new aspects of regulation in host-pathogen interactions, at post-transcriptional levels.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
32
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 58 publications
(39 citation statements)
references
References 33 publications
6
32
1
Order By: Relevance
“…Together, these studies indicate that the expression of multiple miRNAs is upregulated post-mycobacterial infection, which may benefit host defense mechanisms against mycobacteria. However, previous studies found that the expression of miR-27b in human monocyte-derived macrophages (MDMs) was different from that stated in our data (35). The contradiction in the expression of miR-27b between our findings using macrophages and those of others using human MDMs may be due to the difference in cell types, time of infection, and growth phases of the bacteria.…”
Section: Discussioncontrasting
confidence: 99%
“…Together, these studies indicate that the expression of multiple miRNAs is upregulated post-mycobacterial infection, which may benefit host defense mechanisms against mycobacteria. However, previous studies found that the expression of miR-27b in human monocyte-derived macrophages (MDMs) was different from that stated in our data (35). The contradiction in the expression of miR-27b between our findings using macrophages and those of others using human MDMs may be due to the difference in cell types, time of infection, and growth phases of the bacteria.…”
Section: Discussioncontrasting
confidence: 99%
“…Recent reports have shown differential expression of host microRNA (miRNA) in response to mycobacterial exposure [20][21][22][23]. Using a set of filtration methods, we retrieved information from several databases to identify a set of miRNAs that target the 43 DMGs.…”
Section: Justification Of the Bcg Responder Module By Validation Agaimentioning
confidence: 99%
“…Recent studies report an altered expression of miRNA-146 and miRNA-155 in case of Helicobacter pylori infection [ 76 ], Listeria monocytogenes [ 77 ], Mycobacterium tuberculosis [ 78 ], and Salmonella enterica [ 79 ].…”
Section: Circulating Mirnas As Biomarker For Sepsismentioning
confidence: 99%